-6(7y-4)=31-3y

Simple and best practice solution for -6(7y-4)=31-3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(7y-4)=31-3y equation:


Simplifying
-6(7y + -4) = 31 + -3y

Reorder the terms:
-6(-4 + 7y) = 31 + -3y
(-4 * -6 + 7y * -6) = 31 + -3y
(24 + -42y) = 31 + -3y

Solving
24 + -42y = 31 + -3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3y' to each side of the equation.
24 + -42y + 3y = 31 + -3y + 3y

Combine like terms: -42y + 3y = -39y
24 + -39y = 31 + -3y + 3y

Combine like terms: -3y + 3y = 0
24 + -39y = 31 + 0
24 + -39y = 31

Add '-24' to each side of the equation.
24 + -24 + -39y = 31 + -24

Combine like terms: 24 + -24 = 0
0 + -39y = 31 + -24
-39y = 31 + -24

Combine like terms: 31 + -24 = 7
-39y = 7

Divide each side by '-39'.
y = -0.1794871795

Simplifying
y = -0.1794871795

See similar equations:

| 3(4x-6)-4-(2x+5)= | | 4(-5+x)=15+3x | | 2x-13+4x=-1+6(x-2) | | 4(-5+x)=15+3 | | 25=-4(8a+2) | | -25=-3+8(x-4) | | 2n+5n=-28 | | 4x^4+33X^2+8=0 | | 21-5v=8(6v-9) | | 2(x-8)=6(x+2) | | 37=7+62 | | -9c-7-3=-29 | | 129-2x=25x+18 | | (6x-2)-(3x-1)=29 | | 3x+5=25-x | | x^3-10x^2+36x-36=0 | | 7(2-5x)=30 | | 50=16f+2 | | 24+9d=-3 | | -5a-6a=-15 | | ?x-2=0 | | -5a-6h=-15 | | 7m(60)= | | 0.06x+0.0575y=588.75 | | 3x+(-x+10)=26 | | 133+200+272+313+368+417+452+487+519+551+583+616+648+679+710+741+769+795+821+843+866+890+911+930+954+989= | | 8x^2-26x+5=0 | | (18-2x)+5x=36 | | -x^2-16x-7=0 | | -4.9t^2+6.5t+7=0 | | 3m-15=21 | | 35=-2r+r^2 |

Equations solver categories